Aireadores de vórtice como sistemas eficientes de oxigenación para el cultivo de tilapia en estanques de geomembrana (2018)
This is the abstract: The intensification of the culture of red tilapia (Oreochromis sp), requires more efficient systems of aeration of the water of the ponds to maintain constant levels of dissolved oxygen, which improve growth rates and feed conversion at a low cost, so this study sought to determine the efficiency of the vortex aerator in a closed system, with recirculation of water, for which red tilapia fingerlings weighing 3 grams were used. A treatment with three replicas was established for 90 days, adapting a hydraulic system with vortex aerator, in circular geomembrane tanks with Biofloc system. A cross-sectional, descriptive study was carried out, contrasting the association between the oxygen levels of the water in the ponds, with the variables of water quality parameters such as pH, ammonium and temperature. The results obtained were processed in the statistical package SPSS version 21. It was evidenced that the association of oxygen levels, measured in parts per million, was directly proportional to the change in pH and temperature, while ammonium levels measured in milligrams per liter, they were maintained despite the variations in oxygen at the end of the crop. The system supported up to 90 grams of weight. As conclusion it was evidenced, that the type of system evaluated, showed greater weight gains, compared to other types of traditional systems, reported in the literature. © 2018 Zootaxa. All rights reserved.